Islam di Panggung Politik Indonesia: Latar Belakang, Dinamika, dan Pergeserannya - Abdul Gaffar Karim (Faculty of Social and Political Sciences, Universitas Gadjah Mada, 1997)
This study is about the background, dynamics, and chonges of Islam in Indonesian politics. It tries to explain comprehensively the position ond problems of Islamic politics in the political setting of modern Indonesia. It will be argued here that there are at least three specific characteristic of Islam in Indonesia. First character is the existence of a myth about the crack between Islam and the State – which has beenfound since the age of Mataram. The second character is a double-standard strategy used by the state. Such strategy make the Islam is obtained differently as a social phenomenon and as a political power. As a social phenomenon Islam is one of the most important base of legitimation for the state. While as a political power, it becomes a target of repressive political restriction by the state. The third character is that the Muslim scholars and activists still have different perceptions on the way Islam contribute and act in the context of the nation politics. Those three characterislics have been the basis of problems and challenges toward Indonesian Islam in the political context.